Effect of Leg Half-Squat Training With Blood Flow Restriction Under Different External Loads on Strength and Vertical Jumping Performance in Well-Trained Volleyball Players - Jiaoqin Wang; Honghao Fu; QiangZhang; Ming Zhang; Yongzhao Fan (SAGE Publishing, 2022)
Purpose To examine the effect of blood flow restriction resistance training under different external loads on the muscle strength and vertical jumping performance in volleyball players. Methods 18 well-trained collegiate male volleyball players were randomly divided into 3 groups: high-load resistance training group (HL-RT, 70% 1RM, n = 6), low-load blood flow restriction resistance training group (LL-BFR-RT, 30% 1RM, 50% arterial occlusion, n = 6), and high-load blood flow restriction resistance training group (HL-BFR-RT, 70% 1RM, 50% arterial occlusion, n = 6). Participants performed leg half-squat exercise 3 times per week for 8 weeks. Measurements of Isokinetic peak torque of knee extension and flexion, 1RM leg half-squat, squat jump, and 3 footed take-off were obtained before and after training. A two-way repeated-measures analysis of variance was used to examine differences among the 3 groups and between the 2 testing time (pre-test vs post-test). Results (1) The HL-RT group was significantly greater in muscle strength than that in the LL-BFR-RT group ( P < .05), but no improvement in vertical jumping performance ( P >.05). (2) Improvement in muscle strength and vertical jumping performance was significantly greater in the HL-BFR-RT group than that in the LL-BFR-RT group ( P <.05). (3) The HL-BFR-RT group had greater but not significant improvement in muscle strength and vertical jumping performance than that in the HL-RT group. Conclusions Although increases in muscle strength were observed between training groups, HL-BFR-RT increased not only muscle strength but vertical jumping performance to a greater extent compared to LL-BFR-RT and HL-RT.